Influence of Negative Life Events on Depression Among In-School Adolescents In Southwest Nigeria - Olu, Ibimiluyi Francis; Oluwayemisi, Fasina Bosede; Bamidele, Iretor-Oscar Oluwaseun (Advances in Social Sciences Research Journal, 2020)
This study investigated the influence of various negative life events on adolescent depression among in-school adolescents in Southwest Nigeria and whether there is gender difference in the association. The descriptive research of the survey type was adopted for the study. The population of the study was all the adolescents, both male and female, in all secondary schools in the southwest of Nigeria. A total of 1650 adolescents between the ages of 12 and 18 years were selected using multistage sampling technique. A self designed questionnaire titled “Assessment of Negative Life Events and Depression Scale” (ANLEDS) was used to elicit information from respondents. The instrument was validated and the reliability was ensured using test re-test method. The reliability co-efficient was 0.75 at 0.05 level of significance. The data collected were analyzed using descriptive analysis for the general question raised while hypotheses 1 was tested using Pearson Product Moment Correlation and hypotheses 2 was tested using student’s t-test at 0.05 level of significance. The result showed that negative life experiences are significantly related to the development of depressive symptoms among adolescents and the association is influenced by gender difference. Based on the findings, it was recommended that school counsellors should organize programmes to create more awareness and encourage adolescents to discuss their challenges with a view to reducing adolescent depression in Southwest Nigeria.